Extent of structural change during the reaction and its relationship to isoselectivity in polypropylene polymerization with ansa‐zirconocene/borate catalyst: A computational study. Issue 30 (9th August 2019) - Orimoto, Yuuichi; Shirane, Satoru; Aoki, Yuriko
Abstract : The mechanism of isotactic polypropylene (iPP) polymerization with an ( R, R )‐ ansa ‐zirconocene/borate catalyst system was analyzed using quantum chemistry (QC) calculations by focusing on the extent of structural change during monomer insertion. The activation energy for migratory insertion, E a, was compared for four possible reaction paths with regard to monomer coordination, that is, 1, 2‐ re, 1, 2‐ si, 2, 1‐ si, and 2, 1‐ re, until the seventh monomer insertion step, explicitly including a borate anion cocatalyst. This indicated that the 1, 2‐ re path was most favorable, except for the first step, which favored 1, 2‐ si . As far as the first step, the product of 1, 2‐ si is a conformational isomer to that of the 1, 2‐ re path, and the exceptional favorability of 1, 2‐ si does not affect the isoselectivity. These results support previous studies, except that our results address the unexplored seventh insertion step with a borate anion cocatalyst by QC calculations. The isoselectivity correlated with the extent of structural change in the whole system during the reaction. It was proved from our detail analysis that the advantage of 1, 2‐ re with a small E a is attributed to its smaller structural changes due to low steric repulsion in the system compared with other paths. Conversely, larger repulsion in the systems involved in other paths results in larger structural changes to minimize the structural strain. However, the relaxation appears insufficient due to structural restriction of the enforced four‐membered ring transition state structure. A borate anion cocatalyst broke the C 2 symmetry of the electronic structures of zirconocene, resulting in an odd–even E a frequency for the monomer insertion. Molecular orbital analysis demonstrated that the d–π orbital overlaps can explain the approach direction of the olefin coordination and the bent structure of zirconocene, providing a different viewpoint from previous studies. The potential for catalyst control was discussed based on our results. © 2019 Wiley Periodicals, Inc. Abstract : Isoselectivity in polypropylene polymerization with an ( R, R )‐ ansa ‐zirconocene/borate catalyst correlates with the "extent" of structural change in the whole system during the reaction. The advantage of 1, 2‐ re with a small activation energy is attributed to its smaller structural changes due to low steric repulsion in the system compared with other pathways. 1, 2‐ re is the most economical pathway.